Landscape ecological risk assessment and driving mechanism of coastal estuarine tidal flats—A case study of the liaohe estuary wetlands - Li, Haifu; Su, Fangli; Guo, Chengjiu; Dong, Linlin; Song, Fei; Wei, Chao; Zheng, Yunlong (Frontiers in Environmental Science, 2022)
Estuarine tidal flats are located in the land-sea crisscross-sensitive zone. The degraded and shrinking state of major tidal flat landscapes weakens their ecological role in maintaining the safety of coastal wetlands in the world. However, little attention has been paid to tidal flat landscape evolution and ecological risks due to the tidal flats being located in the periphery of estuarine wetlands. This study was conducted in the tidal flats of the Liaohe estuary wetlands. The GIS spatial analysis and a transition matrix were combined to explore the tidal flat landscape evolution characteristics. The ecological risk faced by the tidal flats was evaluated by a landscape ecological risk model constructed by landscape indexes. The key driving factors and threshold values that affect the ecological risks were clarified using geographical detectors and regression analysis methods. The results showed that the tidal flats mainly evolved into a natural wetland before 2000 and rapidly changed into an artificial landscape between 2000 and 2010; the proportion of artificial landscapes then began to decline after 2010. Over the past 30 years, the landscape ecological risk in this area has generally been at a medium risk level. The ecological risk index showed a decreasing trend with the increases in landscape diversity. The low-risk artificial plaques have gradually replaced high-risk and medium-risk plaques of exposed tidal flats and natural wetlands. The study showed that human development activities were the key factors affecting the landscape ecological risks of the tidal flats. River sediment discharge was the key natural factor in maintaining the landscape ecological risk at a stable level. Therefore, the human development activities should be controlled within an appropriate limit, and the material supply of the upstream basin should be guaranteed to maintain the stability of the tidal flat landscape form in the protection and utilization of estuarine tidal flats in the future.